The Effect of Plasma Nitriding Parameters on the Thickness of Nitrided Layers - Pilch, Ondrej; Snahnican, Frantisek; Hruby, Vojtech; Studeny, Zbynek (Manufacturing Technology Journal, 2015)
This paper is aimed at chemical-heat treatment of a selected material. The plasma nitriding layers were applied on the 41CrAlMo7-10 steel. The influence of plasma nitriding parameters on the thickness and microhardness of nitrided layers were investigated. Plasma nitriding was performed at 500°C with a mixture atmosphere of H2 and N2 in the plasma nitriding equipment. The pressure of plasma nitriding process was determined to be 280 Pa. The period of the plasma nitriding process was changeable from 5 to 30 hours. The microstructure and mechanical properties of the nitrided layers were studied by using GDOES spectrometry, optical microscopy, and hardness testing. The depths of the plasma nitriding layers were also estimated using cross-sectional microhardness profiles. Microhardness and surface hardness of mentioned samples were significantly increased. The measurements have shown that the period of plasma nitriding process has a significant influence on the depth of nitriding.
Keywords: Plasma Nitriding; Microhardnes; Nitriding Period; Nitrided Layer